Management of bladder cancer : a comprehensive text with clinical scenarios - Chang, Sam S. (Urologist); Konety, Badrinath R. (New York : Springer, 2015)
This book provides a single, comprehensive reference source that incorporates the epidemiology, natural history, and the latest genetic and molecular biological findings of bladder cancer. This book discusses the diagnostic and staging evaluation of both non-muscle invasive and invasive bladder cancer and incorporates the new findings on markers for the diagnosis of bladder cancer. Risk stratified treatment of non-muscle invasive bladder cancer including various approaches to intravesical therapy are reviewed. Current guideline-based approaches to management and new data regarding diagnosis and prognostication of muscle invasive bladder cancer is analyzed and summarized. This book covers the application of chemotherapy for muscle invasive and advanced disease. The evidence-based application of multimodality therapy is highlighted. Gaps in current knowledge and important areas for clinical research are highlighted. Authored by experts in their respective fields, Management of Bladder Cancer: A Comprehensive Text with Clinical Scenarios serves as an easy and complete reference source for clinicians, researchers, individuals in training, allied health professionals and medical students in the fields of Urology, Medical Oncology, Radiation Oncology, Basic and Translational Science and Epidemiology. --
Epidemiology and natural history -- Screening for Bladder Cancer -- Pathology and Staging: Histopathology and Cytopathology -- Pathology and Staging: Genetics and Molecular Biology -- Imaging in Localized and Advanced Bladder Cancer -- New Imaging Techniques in Staging of Urothelial Carcinoma of the Bladder -- Socioeconomic issues and improved quality of care -- Quality of life measures -- Prognostication and risk assessment -- Clinical trials and emerging therapeutic strategies in bladder cancer -- Improved diagnostic techniques -- Clinical scenario: Microscopic hematuria and atypical cytology in a 68 year old man with normal upper tract imaging -- Localized surgical therapy and surveillance -- Clinical Scenario: Initial high grade Ta tumor -- Clinical Scenario: Recurrent Ta tumor -- Clinical Scenario: Rapidly growing, high volume, low grade Ta tumor -- Clinical Scenario: Low grade T1 tumor -- Intravesical therapy -- Clinical Scenario: Initial CIS -- Management of BCG Recurrent Bladder Cancer -- Clinical Scenario: Persistent CIS and HIGH Grade Ta Bladder Cancer after BCG -- Maurizio Brausi -- Clinical Scenario: Presentation and Management of Significant Side Effects from Bacillus Calmette-Guérin Bladder Instillation -- Guideline-based management of non-muscle invasive bladder cancer: comparison of the AUA, EAU, ICUD and NCCN guidelines -- Open Radical Cystectomy -- Robotic cystectomy -- Clinical Scenario: T2 bladder tumor -- Urinary Diversion: Open and robotic techniques -- Chemoradiotherapy -- Clinical Scenario: 53 year-old man with a solitary, 2 cm, high-grade T2 tumor and focal CIS in the bladder dome who wants bladder preservation -- Management of Bladder Cancer, role of chemotherapy and controversies surrounding its application -- Clinical Scenario: Large volume, non metastatic T2 bladder tumor -- The role of pelvic lymphadenectomy at the time of radical cystectomy for bladder cancer -- Clinical Scenario: Unexpected positive nodes at radical cystectomy -- Surveillance and monitoring -- Clinical Scenario: The Role of Perioperative Chemotherapy -- Management of Bladder Cancer with Pelvic Nodal Metastases After Complete Response to Chemotherapy -- Guideline based management muscle-invasive bladder cancer: NCCN, ICUD and EAU
Includes bibliographical references and index
1 13
Keywords: Bladder -- Cancer -- Handbooks; Interventional radiology; Medicine; Oncology; Urology; Oncology -- Handbooks; Urology -- Handbooks